Bilateral Endogenous Endophthalmitis In Association with Knee - Rajwinder Kaur; Shallu Samria; Balbir Khan; Harijot Singh; Kulbir kaur (Delhi Journal of Ophthalmology)
Endogenous endophthalmitis is a rare condition caused by the haematogenous spread of microorganisms from a remote infection site to the eye. Common predisposing conditions are intravenous drug use (IVDU), diabetes, malignancy, immunosuppression, chronic renal failure, parenteral nutrition or invasive medical procedures. Endogenous endophthalmitis with staphylococcal bone infection is rare but a serious condition. We describe a case of bilateral endogenous endophthalmitis in a 32 year old intravenous drug abuser who presented with knee osteomyelitis, which further get complicated to septic pulmonary emboli and infective endocarditis. A high index of suspicion is required to diagnose this condition. Early and aggressive management is the key to the favorable visual outcome.